INDEPENDENT COMMISSIONERS, INSTITUTIONAL OWNERSHIP, FISCAL LOSS COMPENSATION, AND TAX AVOIDANCE: FINANCE AND BANKING SUBSECTOR COMPANIES - Rizki, Marsi Fella; Pasaribu, Maria Margaretty Br; Ameraldo, Fedi (TECHNOBIZ : International Journal of Business, 2024)
This study aims to prove the effect of independent commissioners, institutional ownership, and fiscal loss compensation on tax avoidance in financial and banking subsector companies listed on the Indonesia Stock Exchange in 2019-2023. The research sample totalled 50 companies selected through purposive sampling technique. Based on the results of the research, independent commissioners, institutional ownership, and fiscal loss compensation each have no effect on tax avoidance. Keywords: Independent commissioners, institutional ownership, fiscal loss compensation, tax avoidance